Occupational Stress, Correctional Officers, and Training for the Job: Probing Sources of Stress During the Correctional Service of Canada’s Correctional Training Program - Spencer, Dale (Canadian journal of criminology and criminal justice, 2023)
Occupational stress remains a remarkable problem among correctional officers. While the scholarship on correctional services has scrutinized correctional work to identify and analyze sources and consequences of stress, correctional training has received little attention. Drawing on the literature on sources of stress in corrections work, we analyze and compare whether sources of stress on the job overlap with those of correctional training. We base our analysis on interviews with correctional officers from Canada’s federal prison system who were interviewed while completing the Correctional Service of Canada’s Correctional Training Program. Findings suggest that sources of stress in training are not consistent with those of correctional work. The training program conditions succeed in preparing recruits to manage pressure, strain, and anxiety. However, the program does not necessarily equip recruits to deal with on-the-job stress, and does little to eliminate the occupational stressors and mental health disorders that too often emerge during occupational tenure. Correctional training programs in Canada and beyond must ensure that recruits are equipped with tools to deal with the specific sources of stress and possibly eliminate such sources in the course of work.